Perceptions of Medical Students in King Abdulaziz University about Teaching and Learning Modalities; Comparative Cross Sectional Study between Traditional and System-based Curriculum - Adnan A. Al-Mazrooa,; Nasra N. Ayoub,; Basem S. El-Deek,; Samar M. Al Saggaf,; Abdulaziz M. Boker, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The undergraduate curriculum of the Medical School-King Abdulaziz University, Saudi Arabia was a traditional one (it was teacher centered, discipline-based, and hospital-based with no options or elective modules). In 2006-2007, the Medical School adopted a new system-based curriculum. This study was constructed to compare the perceptions of students of both, the traditional and new curricula to identify the problem areas that should be remediated. A comparative cross-sectional study was carried out with the third- and fourth-year students at 2008/2009. A questionnaire was distributed to the third-year students who were enrolled in the new system-based curriculum (n = 227 response rate was 80%) and to the fourth-year students who were enrolled in the old curriculum (n = 217 response rate was 76%). For the third-year students, the total mean scores of all the studied domains were significantly higher compared with the fourth year students except for the fourth domain (library and electronic learning resources), which showed an insignificant difference between the two groups. Perceptions of students who experienced the system-based curriculum are significantly higher than those who had experienced the traditional ones; however, the overall score is still low. Therefore, there is a great need for improvement.